SUICIDE BEHAVIOR AS A SOCIAL PROBLEM IN BALI: A SOCIO-LEGAL STUDY AND THE ROLE OF CUSTOMARY VILLAGES AS A PREVENTION MEASURE - I Wayan Eka Artajaya; Dewa Gede Edi Praditha (Universitas Bali Dwipa, 2025)
The phenomenon of suicide in Bali is a complex issue that has not only psychological dimensions, but also social, cultural, and legal dimensions. This study uses a socio-legal approach to examine how suicidal behavior is understood and handled within the framework of customary law and in the context of the local wisdom of the Balinese people. By highlighting the traditional village as a place to ensure community welfare, this paper reveals how values ​​such as communal values ​​of society, the values ​​of karma phala, Tri Hita Karana, and Tat Twam Asi play a role in shaping social responses to suicide. This study also identifies opportunities and challenges in building a suicide prevention system that is contextual and culturally just.